2017
DOI: 10.1097/meg.0000000000000900
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease can be predicted by retinal vascular changes in patients with obesity without hypertension or diabetes

Abstract: NAFLD in patients with obesity without diabetes or hypertension can be predicted by RVC, a noninvasive technique carried out by eye fundoscopy. NAFLD alone can drive inflammatory conditions in the absence of obesity that manifests as RVC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…In a previous published paper we had a group of patients with BMI<25 and NAFLD which showed the higher inflammatory process. So if we had included this fourth group in our present models we probably would found higher alteration in β oxidation and inflammatory markers[ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous published paper we had a group of patients with BMI<25 and NAFLD which showed the higher inflammatory process. So if we had included this fourth group in our present models we probably would found higher alteration in β oxidation and inflammatory markers[ 45 – 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, only one study has con rmed retinal vascular changes as a predictor of NAFLD in obese patients in the absence of diabetes and hypertension which implies the intrinsic role of NAFLD in initiating retinal changes. [35] A link between NAFLD pathophysiology and CT can be justi ed on a molecular basis. Asymmetric dimethyl arginine (ADMA), an endogenous inhibitor of nitric oxide synthase (NOs), plays a critical role in endothelial dysfunction in NAFLD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[41] This study also suggested that CT is inversely associated with homocysteine, albumin, aspartate transaminase (AST), alanine transaminase (ALT) and high-density lipoprotein (HDL) all of which are applicable as biomarkers of NAFLD and hepatic damages. [42,43] Moreover, Romero-Ibarguengoitia et al [35] indicated that non-diabetic thin NAFLD patients with retinal vascular changes (RVC) have higher levels of IL-2, IL-6, TNF-α, and interferon-γ and CRP level independently contributes to higher risk of NAFLD, obesity and RVC.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported the elevation of certain proinflammatory cytokines in NAFLD in patients with BMI less than 25 such as interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) [13,15]. This association has been linked to hepatic pro-regenerative process [15].…”
Section: Discussionmentioning
confidence: 99%
“…A previously published study in a Mexican population demonstrated that non-obese patients with NAFLD showed increased retinal vascular changes and an elevation in pro-inflammatory processes such as C-reactive protein and interleukins compared with obese patients with NAFLD [13].…”
Section: Introductionmentioning
confidence: 99%